Comparison between kinetics of positive inotropism of ibopamine and ouabain - Huang Jun; Dai Yin; Chou Yi-Tang; Hong Xu; Huang Jia-Zi; Yu Feng; Dai De-Zai (Acta Pharmacologica Sinica, 2016)
"AIM: To compare the kinetics of positive inotropism between ibopamine (Ibo) and ouabain (Oua). METHODS: The isolated right papillary muscle of cat was used to assess the positive inotropic effects by cummulative concentrations of Ibo and Oua. The maximal effects was recognized as the contraction just before the appearance of spontaneous contraction. A Hill equation was developed by using lg [E/(Emax-E)] vs lg C. RESULTS: The S value of Ibo was smaller than that of Oua, causing C95/C5 (ratio of concentrations producing 95%/5% of Emax) of Ibo (264) elevenfold as large as Oua (22.9). Comparing with Oua, concentrations of Ibo initiating effects were lower, the slope was smaller, and higher concentrations were required for producing maximal effect. During drug concentration declining, the effect-concentration curve of Ibo showed a counter-hysteresis loop, more remarkable than Oua. CONCLUSION: The changes in positive inotropism of Ibo against drug concentrations were less than those of Oua. "